Importance of the authorship order and number of co authors in a Publication for Evaluation: A Necessary Enquiry - Sathian, Brijesh; Simkhada, Padam; Sreedharan, Jayadevan (Nepal Journal of Epidemiology, 2014)
There is an increasing trend of multi author research papers in the medical and science journals. Multidisciplinary scientific collaboration indeed must be encouraged, but we need to avoid misinterpretations so that current and future scientific communities can evaluate author contributions. First author should know who should be eligible for the authorship. DOI: http://dx.doi.org/10.3126/nje.v4i4.11207 Nepal Journal of Epidemiology 2014; 4(4):384-85